Introducing the concept of centergram. A new tool to squeeze data from separation techniques-mass spectrometry couplings - Guillaume L. Erny (2014)
In separation techniques hyphenated to mass spectrometry (MS) the bulk from the separation step is continuously flowing into the mass spectrometer where the compounds, arriving at each separation time, are ionized and further separated based on their m/z ratio. An MS detector is recognized as being a universal detector, although it can also be a very selective instrument. In spite of these advantages, classical two dimensional representations from these hyphenated systems, such as those based on the base peak of electropherogram/chromatogram or on the total ion of electropherogram/chromatogram, usually hide a large number of features that if correctly assessed will show the presence of co-migrating species and/or the low abundant ones. The uses of peak picking algorithms to detect and measure as many peaks as possible from a dataset allow extracting much more information. However, a single migrating compound usually produces a multiplicity of ions, making difficult to differentiate peaks generated by the same compound from other peaks due e.g., to closely co-migrating/eluting species. In this work, a new representation is proposed and its usefulness demonstrated with experimental data from capillary electrophoresis-hyphenated to a time of flight mass spectrometer via an electrospray interface. This representation, called centergram, is obtained after using a peak picking methodology that detects electrophoretic peaks of single ions and measure their positions. The centergram is the histogram (i.e. the count of the number of observations that fall into each one of the intervals, known as bins, as determined by the user) of the measured positions. The intensity of the bars in this histogram will indicate the amount of peaks in the whole dataset whose centers are within each interval. As a compound that has been separated and has entered the MS instrument will produce multiple images at the same position along the m/z dimension, the centergram will exhibit a series of intense bars around the migration time. Those bars will allow defining a centergram peak whose area will be proportional to the number of different types of ions that have been generated in the ionization chamber, the position will be equal to the migration/retention time of the parent compounds and the width will depend on the precision in the measurement of the peak positions. The efficiency of this peak is determined to be up to thirty times higher than the equivalent peak in the classical base peak electropherogram allowing detecting easily co-migrating peaks or the presence of compounds at very low abundance. The number of peaks detected by using this new tool called centergram was increased by more than a factor of 3 compared to the standard representations.